If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -5) + 4(2x + -1) = 47 Reorder the terms: 3(-5 + x) + 4(2x + -1) = 47 (-5 * 3 + x * 3) + 4(2x + -1) = 47 (-15 + 3x) + 4(2x + -1) = 47 Reorder the terms: -15 + 3x + 4(-1 + 2x) = 47 -15 + 3x + (-1 * 4 + 2x * 4) = 47 -15 + 3x + (-4 + 8x) = 47 Reorder the terms: -15 + -4 + 3x + 8x = 47 Combine like terms: -15 + -4 = -19 -19 + 3x + 8x = 47 Combine like terms: 3x + 8x = 11x -19 + 11x = 47 Solving -19 + 11x = 47 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '19' to each side of the equation. -19 + 19 + 11x = 47 + 19 Combine like terms: -19 + 19 = 0 0 + 11x = 47 + 19 11x = 47 + 19 Combine like terms: 47 + 19 = 66 11x = 66 Divide each side by '11'. x = 6 Simplifying x = 6
| x+6+5x-12+7x-48=180 | | 9/4*9 | | 4x^2+10x-143=0 | | 3p-q=9 | | 1700j+140=4500 | | 0.2(x+30)*.6x=22 | | 24-6=45-90 | | 9/10-2/5= | | 2(x+30)+6x=22 | | x^2-10x+15=-10 | | x+4+4x-8+7x-35=180 | | 0.33333333x+-3=3 | | -0.18/t=-5.2 | | 9x+2+13x-18+17x+1=180 | | 12=z/-9 | | 0=10x^4-24x^3-3x^2 | | 3.2x+6=15 | | x/7+5=-2 | | x/18=2 | | Y-1=X-3 | | 4x-3+9x-6+6x-1=180 | | 8(5-x^2)-3= | | z/7+9=5 | | X^4-13x^3+36= | | 6t-.16666667=9 | | 3(X+1)-2(X-2)=5 | | 18/48 | | 2/5-2/10 | | 5x-4+3=9-x | | -39+x^2=10x | | 42-21x+252=44 | | 6x-27=0findx |